Durable remissions in a pivotal phase 2 study of brentuximab vedotin in relapsed or refractory Hodgkin lymphoma - Gopal, Ajay K; Chen, Robert; Smith, Scott E; Ansell, Stephen M; Rosenblatt, Joseph D; Savage, Kerry J; Connors, Joseph M; Engert, Andreas; Larsen, Emily K; Chi, Xuedong; Sievers, Eric L; Younes, Anas (Blood, 2015)
We present response and survival outcomes of a pivotal phase 2 trial of the antibody-drug conjugate brentuximab vedotin in patients with relapsed/refractory Hodgkin lymphoma following autologous stem cell transplant (N = 102) after a median observation period of approximately 3 years. Median overall survival and progression-free survival were estimated at 40.5 months and 9.3 months, respectively. Improved outcomes were observed in patients who achieved a complete remission (CR) on brentuximab vedotin, with estimated 3-year overall survival and progression-free survival rates of 73% (95% confidence interval [CI]: 57%, 88%) and 58% (95% CI: 41%, 76%), respectively, in this group (medians not reached). Of the 34 patients who obtained CR, 16 (47%) remain progression-free after a median of 53.3 months (range, 29.0 to 56.2 months) of observation; 12 patients remain progression-free without a consolidative allogeneic stem cell transplant. Younger age, good performance status, and lower disease burden at baseline were characteristic of patients who achieved a CR and were favorable prognostic factors for overall survival. These results suggest that a significant proportion of patients who respond to brentuximab vedotin can achieve prolonged disease control. The trial was registered at www.clinicaltrials.gov as #NCT00848926.